Pulmonary paracoccidioidomycosis in the pneumology unit of General Hospital in Recife (Brasil). I. (Boletín Micológico, 1995)
In order to determine the presence of fungi in clinical samples of the respiratory system, 322 patients with pneumopathies were surveyed. All of them had been hospitalised in the Pneumology Unit of the Otavio de FreitasGeneral Hospital, Recife, PE, Brazil. Paracoccidioidomycosis was diagnosed in 7 male patients (2.1%), and involved with work in the rural zone. In 6 cases there was a "diagnostic mistake" between pulmonary tuberculosis andpulmonary paracoccidioidomycosis; in 1 case the association of these two pneumopathies was verified.